Anxiety and Depression Symptoms During the COVID-19 Pandemic: A Cluster Analysis of Individuals Living in Portugal - Aguiar, Ana (2023)
Introduction: The COVID-19 pandemic is an illustration of how a physical illness can damage people’s minds. In this regard, the goal of this study was to see how different sociodemographic and behavioral factors were linked to anxiety and depression symptoms in a group of individuals living in Portugal. Methods: Between November 2020 and February 2021, a cross-sectional, snowball online study was conducted. The study’s target population was adults over the age of 18, residents of the country. For the statistical analysis, the clustering technique – K-means algorithm was applied. The chi-squared test was used to determine the relationships between clusters and sociodemographic and behavioral characteristics. Statistical analyses were conducted in R language, with a significance level of 0.05. A total of 453 participants were included. Results: The majority were female (69.8%), under the age of 40 (60.8%), with a higher education degree (75.3%), and not married (54.4%). Furthermore, the majority were from the country’s north region (66%). Cluster 1 (n = 194) was characterized by low or nonexistent levels of anxiety and depression symptoms, which means normal; cluster 2 by severe symptoms (n = 82), meaning case; and cluster 3 by mild symptoms (n = 177), which means borderline. Younger participants (p-value 0.024), female (p-value 0.041), with drinking habits (p-value 0.002), food insecurity (p-value < 0.001), food affordability exacerbation (p-value < 0.001), comorbidity (p-value < 0.001), use of anxiolytics (p-value < 0.001), insufficient household income (p-value 0.017) and income change (p-value < 0.001) were significantly associated with the anxiety-depression clusters. From the three clusters, cluster 2 was mainly represented by younger participants, with more persons stating that their household income was insufficient and that their income has changed as a result of COVID-19 and that they had the highest probability of food insecurity. Conclusion: The impacts of a crisis on mental health extend longer than the event itself. We were able to observe that younger women with insufficient household income who suffered a change in income due to COVID-19 and were classified as food insecure presented higher levels of anxiety and depression symptoms. These results highlight the presence of a social gradient where we saw that people who were less advantaged in terms of socioeconomic position presented worse mental health outcomes, stressing, in this sense, the need to bring the best public health responses for these specific groups of the population.